Even Central Users Do Not Always Drive Information Diffusion. - CHAO GAO; ZHEN SU; JIMING LIU; KURTHS, JÜRGEN (Communications of the ACM, 2019)
The article looks at how central users do not always contribute to information diffusion due to how diffusion processes interact. It examines how a community structure can decrease the stability of such crossover points and discusses the increment of source nodes.